Targeted Inhibition of GATA-3 by Pyrrothiogatain: Implications for Adipocyte Biology and Inflammatory Response - Shamma Almuraikhy; Maha Alser; Khaled Naja; Aisha Al-Malki; Nayef A. Mazloum; Mohamed A. Elrayess (Cells)
GATA-3 is a master regulator of preadipocyte differentiation and function. Pharmacological or genetic targeting of GATA-3 will allow us to understand the function of GATA-3 in regulating metabolism, insulin signaling, and inflammation. Pyrrothiogatain, a novel small molecule inhibitor of GATA family proteins, has emerged as a promising tool for modulating GATA-3 activity. This study aims to investigate the specificity of Pyrrothiogatain in regulating GATA-3-mediated preadipocyte differentiation and adipokine secretion under normal and pathological conditions. Wild-type and GATA-3 knockout 3T3-L1 cells were treated with different concentrations of Pyrrothiogatain in the presence and absence of 4-hydroxy-2-nonenal (4HNE), an inducer of oxidative stress and impairment of adipogenesis. As expected, GATA-3 knockout cells exhibited enhanced adipogenic capacity, characterized by increased cell and lipid droplet sizes, and upregulated expression of key adipogenic markers including CEBPβ, PPARγ, and PGC-1α. Pyrrothiogatain treatment reduced cell proliferation in both wild-type and GATA-3 knockout 3T3-L1 cells, but did not alter their adipogenic capacity. Furthermore, Pyrrothiogatain lowered secreted IL-6 levels and attenuated 4-HNE-induced TNF-α elevation in wild-type, but not in GATA-3 knockout cells. Co-treatment of 4-HNE and Pyrrothiogatain led to increased cell size, suggesting complex interactions between oxidative stress and GATA protein inhibition. This effect was similar to GATA-3 knockout cells, indicating Pyrrothiogatain’s potential to modulate cellular stress responses independently of GATA-3 inhibition. These results reveal that Pyrrothiogatain’s effects on adipocyte biology extend beyond simple GATA-3 inhibition. While GATA-3 knockout primarily affects adipogenesis, Pyrrothiogatain modulates inflammatory responses and potentially cellular stress mechanisms without directly impacting adipocyte differentiation. This study provides new insights into the multifaceted actions of Pyrrothiogatain and highlights its potential as a therapeutic agent for lowering inflammation and oxidative-stress-related aspects of metabolic disorders, distinct from the direct modulation of adipogenesis.